Tax collection efficiency and tax revenue generation in Nigeria - Ibrahim Solomon Audu; Olalekan Akinrinola; Teju Somorin (Center of Research and Innovation Strengthen LP2M UNM, 2023)
When compared to other African countries, Nigeria has one of the lowest tax to GDP ratios among the top ten largest countries in Africa. Hence, this study assessed the effect of tax collection efficiency on the level of tax revenue in Nigeria. The study is built theoretically on the cost-benefit theory of taxation. Secondary data was collected in this study over an eleven-year time period which range over 2011 to 2021. The data were processed analytically using the regression model to measure the effect of the independent variable which is tax cost of collection efficiency on the dependent variables which are direct cost and indirect taxes and moderated by accountability of the collecting agency. The outcome of the study shows the regression result of 74.3% and a calculated p-value of 0.002 which shows that tax collection cost efficiency have a high level of significance effect on direct tax revenue generation in Nigeria. It is concluded from the result that tax collection cost efficiency does have a significant effect on tax revenue generation in Nigeria. Based on the outcome of the study, it is advised that more prudent measures be set up so as to ensure improvement in the tax collection process in order to manage tax collection cost efficiently and improve tax revenue generation in Nigeria.